If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 28 = 16x + -52 Reorder the terms: 28 + 6x = 16x + -52 Reorder the terms: 28 + 6x = -52 + 16x Solving 28 + 6x = -52 + 16x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-16x' to each side of the equation. 28 + 6x + -16x = -52 + 16x + -16x Combine like terms: 6x + -16x = -10x 28 + -10x = -52 + 16x + -16x Combine like terms: 16x + -16x = 0 28 + -10x = -52 + 0 28 + -10x = -52 Add '-28' to each side of the equation. 28 + -28 + -10x = -52 + -28 Combine like terms: 28 + -28 = 0 0 + -10x = -52 + -28 -10x = -52 + -28 Combine like terms: -52 + -28 = -80 -10x = -80 Divide each side by '-10'. x = 8 Simplifying x = 8
| 327=37+26y | | a=3b-7whatisb | | a=3b-7 | | y=x^2+7x-18 | | 3x^3(2x^3+3x-7)= | | x^3-5x^2+8x-40=0 | | 2+3=5 | | 18y^2-8= | | 1*8n=64 | | x^2+2x=324 | | 16x^2-17x=0 | | (2x+1)(x)-150=0 | | 8w-14w=42 | | 72n-93=504 | | 12+3x=12+x | | 72n-93+n=504 | | 12-2x=15-3x | | 12t^2-66t+54=0 | | 6x+16-5x=-8-10 | | 3(2x-8)-10(9+x)=216 | | 12x+6=10x+10 | | 4x-13=x+90 | | 4-(4x+3)=3x-4(x+5) | | 34x-21=18x+23 | | 2x+6=28 | | 28=9x-80 | | 10x+5=11+6x | | 10x+5=11+6 | | 4y=2y-5 | | 13x+17y=-19 | | 12x^3-52x^2-40x=0 | | 8n+10-6n-15=9 |